John XXI revisited - Sequeira, Álvaro (Portuguese Journal Internal Medicine, 1999)
The author reviews the figure of Pope John XXI. The multiple facets of this figure, including bis medical and philosophical works, as well as the position which he maintained until the end of the 17th century, are discussed. His intervention in the crisis between Portugal and the Vatican in the 13th century, and bis activities as Pope during bis eight months pontificate, are described. His works as a doctor and humanist, are presented and criticised, as well as an attempt made to construct the psychological profile of the man.